Effect of thermomechanical processing via rotary swaging on properties and residual stress within tungsten heavy alloy - Kunčická, Lenka; Macháčková, Adéla; Lavery, Nicholas P.; Kocich, Radim; Cullen, Jonathan C.T.; Hlaváč, Libor M. (International journal of refractory metals & hard materials, 2020)
The effects of cold and warm rotary swaging and subsequent post-process annealing on mechanical properties, residual stress, and structure development within WNiCo powder-based pseudo-alloy were predicted numerically and investigated experimentally. The swaging temperature of 900 °C imparted increase in the Young’s and shear moduli; the post-process annealing at 900 °C also imparted decrease in the residual stress values, primarily due to structure recovery introduced within the matrix. Cold rotary swaging at 20 °C imparted ultimate tensile strength of almost 1 900 MPa, while warm rotary swaging at 900 °C introduced increased plasticity (almost 24 % after a single swaging pass). Post-process heat treatment promoted diffusion of W to the Ni/Co matrix, which increased strength, but remarkably decreased elongation to failure and residual stress. Numerically predicted results of mechanical behaviour corresponded to the experimental results and confirmed the favourable effects of the selected thermomechanical treatments on WNiCo performance. [Display omitted] •THAs were fabricated using cold and warm rotary swaging.•THA featured substantial tensile strength after both swaging regimes.•Increased swaging temperature reduced residual stress.•Heat treatments caused the drop of residual stress but growth of heterogeneity.